Silvopasture and its Impacts to Microclimates, Soil Properties, and Carying Capacity on Semi Arid Grass Land of West Nusa Tenggara Province, Indonesia - WIGENA, I GEDE PUTU (Indonesian Center for Agriculture Land Resource Development, 2011)
In West Nusa Tenggara Province, natural pasture is one of important forage sources for cattle feed. Due to its agroclimate condition, carrying capacity of the native pasture is usually low. Wider variation has been observed between wet and dry seasons, and it has significant effects to cattle population. Based on the issue, a medium term of land management by introducing of silvopasture combined with legume trees, high yielding varieties of grasses, and fast growing leguminous shrubs, has been done during 1995/96-1998/99 period. The aim of the research was to increase carrying capacity of the natural pasture based on the improvement of microclimate condition, soil properties, and carrying capacity. The experiment used split-plot design with three replications. Implementation of silvopasture in the form of wind breaker (WB) and non wind breaker (NWB) are as main plot, carrying capacity estimation (grazing and cut systems) as sub plot, while introducing high yielding varieties of grasses and fast growing legume as sub-sub plot. Observation during four years showed that silvopasture could improve microclimate conditions indicated by decreasing of air temperature from 27.9-40.0oC into 22.0-38.9oC, increasing of air humidity from 62.6-93.6% into 77.1-89.1% and decreasing of saturation steam pressure deficit from 3.4-26.3 into 0.5-14.8. Soil organic matter increased almost 200% on the 3rd year and soil nitrogen increased almost 300% on the 4th year of experiment. Silvopasture system (wind breaker treatment) could increase carrying capacity grass land that varied from 1.16 to 1.75 animal unit (AU) of cattle/ha/year, while carrying capacity of non wind breaker varied from 1.10 to 1.37 animal unit (AU) of cattle/ha/year.